Pemilihan dan Penataan Vegetasi dalam Mengurangi Emisi Karbon Kendaraan di Terminal Purabaya (Program Studi Arsitektur Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2023)
Carbon emission is one of the global problems that many vehicles generate. This is because humans rely on vehicles as a means of facilitating mobility to their destination. One of the most widely used vehicles is the bus vehicle. Terminal Purabaya is a type A bus terminal located in Sidoarjo Regency, East Java, which is very busy. This makes the terminal a significant contributor to carbon emissions due to the high number of vehicles entering and exiting the area. There are various methods that can be employed to reduce carbon emissions, one of which is the most natural approach, utilizing vegetation with the best carbon absorption capacity to decrease the carbon content in the surrounding air. Therefore, the selection of suitable vegetation to reduce carbon emissions at Terminal Purabaya is carried out through data analysis of total carbon emissions and the carbon sequestration capacity of trees. The results will provide the most effective vegetation for carbon reduction at Terminal Purabaya, allowing for appropriate arrangements to be made to mitigate carbon emissions at this terminal.